Peculiarities of surgical management of combined echinococcosis - K. B. Yrysov; N. D. Mamashev (Бюллетень сибирской медицины)
Surgery has remained the mainstay for the management of hydatid cysts. The success of any operation depends to a great extension how well the optimal surgical approach is chosen and which method of residual cyst sanitation. The purpose of the study was to analyze of complications after combined cyst, brain and abdominal, surgery. The complications associate with depth, size and relation to adjacent organs.